Nivolumab-induced immune-mediated neurotoxicity in Hodgkin lymphoma. Issue 1 (2nd January 2020) - Lopez, James; Yarlagadda, Naveen; Gheith, Zaid; Mohan, Meera; Sasapu, Appalanaidu
Abstract: Nivolumab, a monoclonal antibody against programmed cell death-1 used to treat multiple cancers, has fewer side effects than traditional chemotherapy but has displayed a propensity to cause a host of immune-related adverse events. We describe a case of nivolumab immune-mediated neurotoxicity in a 42-year-old Hispanic man with relapsed Hodgkin lymphoma who presented with unilateral facial droop, dysarthria, and dysphagia 1 week after receiving nivolumab. His symptoms rapidly improved with steroids, intravenous immunoglobulin, and infliximab.